P2Y12, a New Platelet ADP Receptor, Target of Clopidogrel - Savi, P.; Labouret, C.; Delesque, N.; Guette, F.; Lupker, J.; Herbert, J.M. (Biochemical and biophysical research communications, 2001)
The binding characteristics of 33P-2MeS-ADP, a stable analogue of ADP, were determined on CHO cells transfected with the human P2Y12 receptor, a novel purinergic receptor. These transfected CHO cells displayed a strong affinity for 33P-2MeS-ADP, the binding characteristics of which corresponded in all points to those observed on platelets. In particular, this receptor recognised purines with the following order of potency: 2MeS-ADP = 2MeS-ATP > ADP = ATPγS = ATP ⪢ UTP, a binding profile which is similar to that obtained in platelets. The binding of 33P-2MeS-ADP was antagonised by pCMPS but not by MRS2179 and FSBA, antagonists of P2Y1 and aggregin, respectively. Moreover, the binding of 33P-2MeS-ADP to these cells was strongly and irreversibly inhibited by the active metabolite of clopidogrel with a potency which was consistent with that observed for this compound on platelets. Like in platelets, 2MeS-ADP induced adenylyl cyclase down-regulation in these P2Y12 transfected CHO cells, an effect which was absent in the corresponding non-transfected cells. As already shown in platelets, the active metabolite of clopidogrel antagonised 2MeS-ADP-induced inhibition of adenylyl cyclase on transfected cells. Our results confirm that P2Y12 is the previously called “platelet P2tAC” receptor and show that this receptor is antagonised by the active metabolite of clopidogrel.